Benefits Variation Teaching Style Using Method Simulation In Learning Ips In Class Vi S D Negeri 17 Batu Kunit Jurai District Iv Academic Year 2014/2015 - Lili Ervo (Fakultas Sastra Universitas Ekasakti, 2017)
Low student learning outcomes in these days can also be caused by the condition and mental development of students . Basic Education aims to provide the basic ability for learners to develop kehidupannva as private, community members, citizens, and as human beings and to prepare learners to follow the next education in social studies. To solve the above problems researchers tried a simulation method in teaching social studies education in SDN No. 17 Stone Kunit the District IV Jurai Regency South Coast of the Academic Year 2014/2015 . By using simulation method is expected to encourage the participation of students, enhancing skills - skills, decision making, utilize the resources associated with the decision - a decision that would be made, to help develop students' attitudes, develop persuasion and communication as well as introducing students to the role of leadership. The general objective of this research is to improve the learning process in the sixth grade social studies education No. 17 Stone Kunit the District IV Jurai Regency of South Pesisir in the school year 2014/2015, by using simulation methods with the aim to eliminate boredom, creates excitement, motivation, improve outcomes and the learning process and critical thinking for students. Implementation of Class Action Research conducted in SDN No. 17 Stone Kunit the District IV Jurai Regency South Coast of the Academic Year 2014/2015. Subject pemelitian is the number of learners Class VI SDN No. 17 Stone Kunit in the school year 2014/2015 amounted to 22 students. Scores obtained by the students in the first cycle is still far below the standard. The average value of the first cycle is a pre-test of 5.16 and 5.99 pe test. Increased 0.83. students who earn top grades 6 to 17 people (51.51%). Meanwhile, students who scored less than 6 there were 16 (48.49%). Based on the analysis of student work in the second cycle also showed an increase in that of the average scores of post test increased to 5.99, 6.43 so there is an increase of 0.44. In the second cycle students who scored 6 and above there are 15 people, and students who scored less than 6 No 7 of the number of students 22 people. Based on the analysis of work of students in the third cycle in general learning results obtained by the students showed an increase. This we compare a score of 5.99, 6.43 second cycle and the third cycle becomes 7.12 of unity cycle up 0.44 kesiklus second and third cycle of unity kesiklus 0.69. The number of students who received a score of 6 and 19 and learners who score below 6 No 3 number of students 22 people. In general, the process of learning social studies using simulation methods can improve results and get a positive response from the majority of students of class VI SDN No. 17 Stone Kunit K ecamatan IV Jurai Regency South Coast of the Academic